2021
DOI: 10.1002/advs.202104006
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine Nanoparticle‐Mediated Dopaminergic Immunoregulation in Colitis

Abstract: Despite immunosuppression is critical for reducing immune overactivation, existing immunosuppressive agents are largely restricted by low inhibition efficiencies and unpredictable off-target toxicities. Here, the use of the dopaminergic system is reported to suppress hyperactive immune responses in local inflamed tissues. A polydopamine nanoparticular immunosuppressant (PDNI) is synthesized to stimulate regulatory T (Treg) cells and directly inhibit T helper 1 (Th1), Th2, and Th17 cells. Moreover, PDNI can inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 52 publications
1
45
0
Order By: Relevance
“…PDA and its derivatives also had potential scavenging effects on excessive reactive oxidative stress (ROS), further alleviating and treating ROS derived diseases such as ischemic stroke, Parkinson and osteoarthritis due to its abundant reductive groups like catechol and imine [ [24] , [25] , [26] , [27] ]. PDAs tended to target dopamine receptors, which were highly expressed in immune diseases including RA, and functions as immune system regulator as well [ 28 ]. Significantly, it had unique property of bioadhesion similar to mussel-adhesive proteins that displayed high adhesion to most substrates [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…PDA and its derivatives also had potential scavenging effects on excessive reactive oxidative stress (ROS), further alleviating and treating ROS derived diseases such as ischemic stroke, Parkinson and osteoarthritis due to its abundant reductive groups like catechol and imine [ [24] , [25] , [26] , [27] ]. PDAs tended to target dopamine receptors, which were highly expressed in immune diseases including RA, and functions as immune system regulator as well [ 28 ]. Significantly, it had unique property of bioadhesion similar to mussel-adhesive proteins that displayed high adhesion to most substrates [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…This self-regulating engineered yeast probiotic inhibits intestinal inflammation and reduces intestinal fibrosis and dysbiosis in IBD mouse models and we think their self-regulating strategy may provide a new way for engineered probiotics to treat IBD or other diseases. Liu Jinyao's team at Shanghai Jiaotong University School of Medicine in China synthesized a polydopamine nano immunosuppressant and used it to coat E. coli Nissle 1917 to inhibit the excessive immune response in the local tissues of mouse colitis and regulate the intestinal microbiota to promote the reversal of inflammation [ 21 ]. Liu et al's study showed that applying immunosuppressants on the surface of beneficial bacteria can promote improved colitis responses in mice.…”
Section: Research and Application Of Engineered Probioticsmentioning
confidence: 99%
“…Recent studies demonstrated that the immune imbalance between CD4 + T cells, Th1/Th2, and Treg might be the most direct and vital factor in the pathogenesis of IBD. It also played a role in mediating the occurrence of ulcerative colitis ( 34 , 35 ). The current study suggested a reducing ratio of Th1/Th2 and Treg in LP alleviated inflammatory response in colonic tissue.…”
Section: Discussionmentioning
confidence: 99%